Students Perception and Willingness to E-learning in Republic of Croatia - Natalija Kokolek; Dajana Ćorić; Božidar Jaković (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
The subject of this paper is e – learning, education process which is held with the use of some form of information and communication technologies to improve the quality of the process and the quality of educational outcomes. New information technologies allow a new attitude to information, digitalization, easy and quickly storing, reproduction, distribution and use. Internet provides us with a variety of opportunities for creativity and the spread of new ideas and knowledge, pushing the boundaries of what we consider our own environment. Through this paper the importance of e - learning as an integral part of the today's educational process will be shown. This paper will take us through the theme of e-learning starting from its definition, historical development of its types, then the technological aspects, statistical information on the topic and it will analyse the survey based on the research. Research on students perception in Republic of Croatia about e-learning will show that Republic of Croatia has a relatively favourable environment for the development and implementation on Croatian universities, and that application of new technologies on the Croatian universities achieves a significant impact on the efficiency of the teaching process.
Keywords: A22; A23; I21; O31; 330; e-learning; education; ICT; Internet